Characterisation of marine penicillium isolates from Bako, Sarawak and their antibiotics - Chan, Olivia Jade Yin (Universiti Malaysia Sarawak (UNIMAS), 2012)
The emergence of multidrug resistant bacteria (MDR) has reduced the efficiency of currently used antibiotics in controlling bacterial infection. Hence, a study was conducted to isolate marine-derived Penicillium sp., and subsequently their antibiotics were characterised. Four marine fungi designated as CASI, CBSI, CCSW and CDSW, were isolated from samples collected from coastal area in Bako, Sarawak. In preliminary screening on Czapek dox agar (CDA) using fungal mycelial discs, the four fungal isolates exhibited strong inhibition zones, which ranged from 17 to 35 mm against Salmonella typhi only. Antibiotics extracts from these isolates were then obtained using hexane and dichloromethane (DCM) solvents. In disc diffusion assay, CAS I hexane extract had strong antibacterial activity against Enterobacter aerogenes even at 0.25 mg/ml. DCM extracts of CBSI and CCSW were active against Staphylococcus aureus at 0.25 mg/ml. On analysis using thin layer chromatography, CAS I hexane extract exhibited four spots with Rfvalues 0.17, 0.43, 0.63 and 0.90, respectively. The TLC plates were cut vertically to form individual strips and were used to perform bioautography assay. Through this assay it was found that fractionated components of CCSW hexane extract exhibited strong antibacterial activity against E. coli, E. aerogenes and S. aureus. The DCM extracts of CBS 1 and CCSW were active against E. coli, S. typhi and S. aureus. Based on macroscopic and microscopic examinations, all the four isolates were identified as Penicillium sp. Molecular identification using primer ITS IIITS4 identified CCSW as Penicillium paxilli (100% similarity). The presence of antibacterial activities with spots that are different from the penicillin-streptomycin control makes it plausible to continue this study with further isolation and characterisation of individual pure compounds.